A Study on The Entry of Islam In Palembang And The Character of Its Society - Aravik, Havis; Achmad Irwan Hamzani; Nur Khasanah; Ahmad Tohir (Jurnal Studi Islam Indonesia (JSII), 2024)
This article discusses Islam's arrival in Palembang and the style of its society. As one of the oldest cities in Indonesia, Palembang in the past was very interesting to study. The existence of Sriwijaya as the most significant maritime kingdom in Southeast Asia and Palembang Darussalam as one of the Islamic sultanates in Indonesia made Palembang one of the centers of great culture and civilization. The arrival of Islam in the city of Palembang is unique. It makes Palembang the Veranda of Medina, proving that the Islam developed in Palembang is good and can be quickly absorbed by the people. The method used is a historical approach, examining sources based on books, papers, journals, and other scientific articles and analyzing them using historical analysis. The results show that Islam in Palembang has a very long history. A new chapter began when Palembang became a sultanate. At this time, each sultan competed to establish Islam in Palembang. The Samaniyah congregation, founded by Shaykh Muhammad bin 'Abd al-Karim al-Samman (d. 1775 AD), was the first congregation that was very popular in Palembang.